Pengaruh Partisipasi Anggaran Terhadap Kinerja Manajerial Dengan Komitmen Organisasi Sebagai Variabel Intervening - Rieuwpassa, Ariel C F; Alimuna, Ririn F; Nurmir, Nurmir (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to examine the effect of budgetary participation on managerial performance with organizational commitment as an intervening variable. Budgetary participation is an important aspect in behavioral management accounting because it involves active manager involvement in the budgeting process, which can influence their attitudes, behavior, and performance. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to middle-level managers and line managers in the organizations/companies used as research objects. Data analysis techniques applied in this study include regression analysis and path analysis to test the direct and indirect influences between variables. The results of the study indicate that budgetary participation has a positive and significant influence on managerial performance. Furthermore, budgetary participation has a positive effect on organizational commitment. Organizational commitment is also shown to have a positive influence on managerial performance and mediates the relationship between budgetary participation and managerial performance. These findings suggest that greater managerial involvement in the budgeting process can increase organizational commitment, which in turn improves managerial performance. This study is expected to contribute to the development of behavioral management accounting literature and provide practical insights for management in designing participatory budgeting systems. This study also emphasizes the importance of behavioral aspects in management control systems and how budgetary participation can be an effective strategy for improving organizational performance. Thus, this study provides new insights into the role of budgetary participation in improving managerial performance through increased organizational commitment.